Anti-static skin-friendly glove material and preparation method thereof

By using natural latex, polyurethane and modified carbon nanotubes in glove materials, anti-static and skin-friendly glove materials are prepared, which solves the static and stability problems of existing latex gloves and achieves the improvement of high mechanical, anti-static and anti-bacterial properties.

CN119708658APending Publication Date: 2025-03-28SHIMU SPECIAL PROTECTIVE EQUIP TECH (JIANGSU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411779474.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-28

Smart Images

  • Figure BDA0005172427520000031
    Figure BDA0005172427520000031
  • Figure BDA0005172427520000032
    Figure BDA0005172427520000032
  • Figure BDA0005172427520000041
    Figure BDA0005172427520000041
Patent Text Reader

Abstract

The invention discloses an anti-static skin-friendly glove material and a preparation method thereof, and belongs to the technical field of glove materials. Comprising the following raw materials in parts by weight: 60-80 parts of natural latex, 20-30 parts of polyurethane, 6-18 parts of modified carbon nanotubes, 3-9 parts of an antioxidant and 2-4 parts of a dispersant. Natural latex is used as a matrix, so that the glove material is endowed with excellent skin-friendly property and mechanical property; wherein the polyurethane can enhance the chemical stability of the glove material and reduce the anaphylaxis of the glove material; wherein the modified carbon nanotubes have good compatibility with a natural latex matrix, can greatly enhance the mechanical properties, antistatic properties and antibacterial properties of the glove material, and have long and stable properties and low possibility of falling off; therefore, the prepared glove material is good in skin friendliness, not prone to allergy, good in chemical stability and excellent in mechanical property, further has stable and efficient antistatic performance and antibacterial performance and has important application value in the technical field of glove materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of glove materials, and in particular, relates to an antistatic skin-friendly glove material and a preparation method thereof. Background Art

[0002] Gloves are hand warming or labor protection products. Common types of gloves are: rubber gloves, nitrile gloves, PVC gloves and latex gloves. Among them, rubber gloves have better elasticity and fit the hands, but have a slight odor and may cause allergies. Nitrile gloves are more skin-friendly than rubber, have slightly worse wear resistance, and are hypoallergenic. They are suitable for medical, food industries and home use. PVC gloves are translucent, thin to the touch, slightly less elastic, safe and odorless, and suitable for home use. Finally, latex gloves are made of natural rubber and are the most skin-friendly of several gloves. They are also soft, wear-resistant and puncture-resistant, acid- and alkali-resistant, suitable for medical and delicate operations, and are widely used in medical and laboratory fields.

[0003] During the use of latex gloves, static electricity will be generated under the action of dynamic stress and friction, which will affect the performance of natural latex gloves. Especially in highly sensitive environments, such as the electronics industry or laboratories, static electricity may damage products or experiments. In order to eliminate static electricity in gloves, technicians generally add antistatic agents to the raw materials to improve the antistatic properties of latex gloves. However, due to the poor compatibility of antistatic agents with natural latex, or easy precipitation and shedding, the stability of the antistatic properties of latex gloves is not good. In addition, after long-term use of gloves, sweat is not absorbed, and bacteria are easily bred in a humid environment, increasing the risk of infectious diseases. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of glove material technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide an antistatic skin-friendly glove material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A method for preparing an antistatic skin-friendly glove material comprises the following steps:

[0007] The natural latex, polyurethane, modified carbon nanotubes, antioxidant and dispersant are mixed in a high-speed mixer, and then put into a twin-screw extruder for melt blending and extrusion to obtain an antistatic skin-friendly glove material.

[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 60-80 parts of natural latex, 20-30 parts of polyurethane, 6-18 parts of modified carbon nanotubes, 3-9 parts of antioxidants, and 2-4 parts of dispersants.

[0009] Furthermore, the extrusion temperature of the twin-screw extruder is 180-200°C.

[0010] Furthermore, the dispersant is one of paraffin and epoxidized soybean oil.

[0011] Furthermore, the antioxidant is prepared by compounding a hindered phenol antioxidant and a phosphite antioxidant in a mass ratio of 2:1.

[0012] With natural latex as the matrix, the glove material is endowed with excellent skin-friendliness, high elasticity and high toughness; the addition of polyurethane can enhance the chemical stability of the glove material and reduce the allergic reaction of natural latex; finally, the added antioxidants are hindered phenol antioxidants and phosphite auxiliary antioxidants, which can play a synergistic role and greatly improve the antioxidant properties of the glove material.

[0013] Furthermore, the modified carbon nanotubes are prepared by the following steps:

[0014] S1. At room temperature, under nitrogen protection, isocyanuric acid was dissolved in deionized water in a three-necked flask equipped with a stirring device, sodium hydroxide was added after stirring evenly, and 5-chlorovaleraldehyde was slowly added dropwise to the three-necked flask. Under magnetic stirring, the reaction was fully reacted at room temperature for 12 hours. After the reaction was completed, the pH was adjusted to 6-7 with dilute sulfuric acid (mass fraction 8%), and the solvent was removed with a rotary evaporator. Then, the mixture was washed with anhydrous ethanol for 3-4 times and dried in vacuo to obtain intermediate 1; the ratio of isocyanuric acid, deionized water, sodium hydroxide and 5-chlorovaleraldehyde was 14.1g:100mL:7.9g:11.9g;

[0015] Isocyanuric acid reacts with 5-chlorovaleraldehyde, and the intermediate 1 is obtained by controlling the molar ratio of the two to be close to 1:1 and the isocyanuric acid to be slightly excessive. The specific reaction process is as follows:

[0016]

[0017] S2, in a three-necked flask equipped with a stirring device, add intermediate 1 and N, N-dimethylformamide (DMF), stir evenly, then add p-phenylenediamine and piperidine (condensing agent), stir and mix evenly, control the reaction temperature to 65 ° C, keep the reaction for 8 hours, the reaction is completed, and part of the solvent is removed by reduced pressure distillation, and then purified by column chromatography (eluent using a mixed solvent of ethyl acetate / benzene, the volume ratio of the two is 5:2), and the eluent is removed by rotary evaporation to obtain intermediate 2; the ratio of the amount of intermediate 1, N, N-dimethylformamide, p-phenylenediamine, and piperidine is 21.3g:100mL:15.2g:15mL;

[0018] Under the action of the condensing agent, the aldehyde group on the intermediate 1 condenses with the amino group on the p-phenylenediamine to form a C=N Schiff base structure. By controlling the molar ratio of the two to be close to 1:1 and the p-phenylenediamine to be slightly excessive, the intermediate 2 is obtained. The specific reaction process is as follows:

[0019]

[0020] S3. In a three-necked flask equipped with a stirring device, carboxylated carbon nanotubes and N,N-dimethylformamide were mixed, and the carboxylated carbon nanotubes were evenly dispersed by ultrasonic treatment for 30 minutes, and then intermediate 2 and dicyclohexylcarbodiimide (DCC) were added, and magnetic stirring was performed for 2 hours. The mixture was placed in a 55°C water bath and ultrasonicated for 2 hours. The water bath was removed and magnetic stirring was performed at room temperature for 8 hours. The mixture was filtered, washed with anhydrous ethanol for 3-4 times, dried, and ground to obtain intermediate 3. The ratio of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate 2, and DCC was 1 g:100 mL:8.4 g:4.3 g.

[0021] Under the action of DCC, -COOH on the surface of carboxylated carbon nanotubes undergoes an amidation reaction with -NH2 on intermediate 2, and organic molecules are grafted on the surface of carbon nanotubes to obtain intermediate 3. The specific reaction process is as follows:

[0022]

[0023] S4. In a three-necked flask equipped with a stirring device, the intermediate 3 was mixed with a mixed solvent of tert-butanol and water (the volume ratio of tert-butanol and water was 4:1), and magnetic stirring was performed for 2 hours. After uniform dispersion, sodium hypochlorite was added, and the mixture was reacted at room temperature for 6 hours under light-proof conditions. After the reaction was completed, the solvent was removed by vacuum distillation to obtain modified carbon nanotubes; the ratio of the intermediate 3, the mixed solvent of tert-butanol and water, and the sodium hypochlorite was 1 g: 100 mL: 15 mL;

[0024] Under the action of sodium hypochlorite, the NH bond in the intermediate 3 molecule is converted into an N-Cl bond. The specific reaction process is as follows:

[0025]

[0026] Carbon nanotubes have excellent electrical conductivity, mechanical properties and a certain degree of antibacterial properties. By modifying carbon nanotubes and grafting hydrophobic groups on their surfaces, the compatibility of carbon nanotubes with natural latex matrix can be greatly improved, thereby promoting the uniform dispersion of modified carbon nanotubes in the matrix, reducing the occurrence of agglomeration, giving full play to the performance of carbon nanotubes, and greatly enhancing the antistatic properties, mechanical properties and a certain degree of antibacterial properties of the matrix; not only that, the modified carbon nanotubes also contain halamines, Schiff bases, and benzene ring structures, among which halamines are cyclic halamine compound molecular structures, and a large number of active chlorine atoms are introduced, which have broad-spectrum and high-efficiency antibacterial properties, and compared with other types of antibacterial agents, it is not easy for microorganisms to develop drug resistance, and has good stability, regeneration and durability; in addition, the introduced Schiff base structure can interact with proteins and enzymes, hinder the synthesis of bacterial nucleotides and amino acids, and synergize with carbon nanotubes and halamines to significantly enhance the antibacterial properties of the matrix; finally, the introduced benzene ring belongs to a rigid group, which can further enhance the mechanical properties of the matrix;

[0027] It should be noted that the grafting of organic molecular chains onto carbon nanotubes can effectively prevent the migration and infiltration of organic molecules, thus ensuring the long-term stability of the performance of the modified carbon nanotubes.

[0028] Furthermore, the carboxylated carbon nanotubes are prepared by the following steps:

[0029] The carbon nanotubes are placed in a conical flask, and then mixed acid is added, and ultrasonic treatment is carried out in a 50°C water bath for 8 hours. After the reaction is completed, the carbon nanotubes are cooled to room temperature, and deionized water is added for dilution, centrifuged, and washed with anhydrous ethanol and deionized water for 4-5 times in sequence, dried, and ground to obtain carboxylated carbon nanotubes; the mixed acid is prepared by mixing concentrated sulfuric acid with a mass fraction of 98% and concentrated hydrochloric acid with a mass fraction of 36.6% in a volume ratio of 2:1; the ratio of the amount of carbon nanotubes to the mixed acid is 1g:100mL;

[0030] By subjecting carbon nanotubes to ultrasonic and oxidation treatment with strong acid, a certain number of carboxyl active groups can be introduced into the side walls and tops of the carbon nanotubes to obtain carboxylated carbon nanotubes.

[0031] Beneficial effects of the present invention:

[0032] 1. The glove material prepared by the present invention uses natural latex as a matrix, which gives the glove material excellent skin affinity and mechanical properties;

[0033] 2. Adding polyurethane can enhance the chemical stability of glove materials and reduce the allergy of glove materials;

[0034] 3. By modifying carbon nanotubes, compared with ordinary carbon nanotubes, they have better compatibility with the natural latex matrix, which can greatly enhance the mechanical properties, antistatic properties and antibacterial properties of the glove material, and the performance is long-lasting and stable, and not easy to fall off;

[0035] Therefore, the glove material prepared by the present invention has good skin affinity, is not prone to allergies, has good chemical stability, excellent mechanical properties, and also has stable and efficient antistatic and antibacterial properties, and has important application value in the field of glove material technology. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Embodiment 1

[0038] Preparation of modified carbon nanotubes:

[0039] S1. At room temperature, under nitrogen protection, 14.1 g of isocyanuric acid was dissolved in 100 mL of deionized water in a three-necked flask equipped with a stirring device. After stirring evenly, 7.9 g of sodium hydroxide was added, and then 11.9 g of 5-chlorovaleraldehyde was slowly added dropwise to the three-necked flask. Under the action of magnetic stirring, the reaction was fully reacted at room temperature for 12 h. After the reaction was completed, the pH was adjusted to 6 with dilute sulfuric acid (mass fraction 8%), and the solvent was removed with a rotary evaporator. The mixture was washed with anhydrous ethanol for 3 times and dried in vacuo to obtain intermediate 1.

[0040] S2, in a three-necked flask equipped with a stirring device, add 21.3g of intermediate 1 and 100mL of N,N-dimethylformamide, stir evenly, then add 15.2g of p-phenylenediamine and 15mL of piperidine, stir and mix evenly, control the reaction temperature to 65°C, keep the reaction for 8h, the reaction is completed, and part of the solvent is distilled off under reduced pressure, and then purified by column chromatography (eluent adopts a mixed solvent of ethyl acetate / benzene, the volume ratio of the two is 5:2), and the eluent is removed by rotary evaporation to obtain intermediate 2;

[0041] S3. In a three-necked flask equipped with a stirring device, 1 g of carboxylated carbon nanotubes was mixed with 100 mL of N,N-dimethylformamide, and ultrasonicated for 30 min to evenly disperse the carboxylated carbon nanotubes. Then, 8.4 g of intermediate 2 and 4.3 g of dicyclohexylcarbodiimide were added, and magnetic stirring was performed for 2 h. The mixture was placed in a 55°C water bath and ultrasonicated for 2 h. The water bath was removed and magnetic stirring was performed for 8 h at room temperature. The mixture was filtered, washed with anhydrous ethanol for 4 times, dried, and ground to obtain intermediate 3.

[0042] S4. In a three-necked flask equipped with a stirring device, 1 g of intermediate 3 was mixed with 100 mL of a mixed solvent of tert-butanol and water (the volume ratio of tert-butanol and water was 4:1), and magnetically stirred for 2 h. After uniform dispersion, 15 mL of sodium hypochlorite was added, and the mixture was reacted at room temperature for 6 h in the dark. After the reaction was completed, the solvent was removed by reduced pressure distillation to obtain modified carbon nanotubes.

[0043] Embodiment 2

[0044] Preparation of modified carbon nanotubes:

[0045] S1. At room temperature, under nitrogen protection, 28.2 g of isocyanuric acid was dissolved in 200 mL of deionized water in a three-necked flask equipped with a stirring device. After stirring evenly, 15.8 g of sodium hydroxide was added, and then 23.8 g of 5-chlorovaleraldehyde was slowly added dropwise to the three-necked flask. Under the action of magnetic stirring, the reaction was fully reacted at room temperature for 12 h. After the reaction was completed, the pH was adjusted to 6 with dilute sulfuric acid (mass fraction 8%), and the solvent was removed with a rotary evaporator. The mixture was washed with anhydrous ethanol for 3 times and dried in vacuo to obtain intermediate 1.

[0046] S2, in a three-necked flask equipped with a stirring device, add 42.6g of intermediate 1 and 200mL of N,N-dimethylformamide, stir evenly, then add 30.4g of p-phenylenediamine and 30mL of piperidine, stir and mix evenly, control the reaction temperature to 65°C, keep the reaction for 8h, the reaction is complete, and part of the solvent is removed by reduced pressure distillation, and then purified by column chromatography (eluent adopts a mixed solvent of ethyl acetate / benzene, the volume ratio of the two is 5:2), and the eluent is removed by rotary evaporation to obtain intermediate 2;

[0047] S3. In a three-necked flask equipped with a stirring device, 2 g of carboxylated carbon nanotubes were mixed with 200 mL of N,N-dimethylformamide, and ultrasonicated for 30 min to evenly disperse the carboxylated carbon nanotubes. Then, 16.8 g of intermediate 2 and 8.6 g of dicyclohexylcarbodiimide were added, and magnetic stirring was performed for 2 h. The mixture was placed in a 55°C water bath and ultrasonicated for 2 h. The water bath was removed and magnetic stirring was performed at room temperature for 8 h. The mixture was filtered, washed with anhydrous ethanol for 4 times, dried, and ground to obtain intermediate 3.

[0048] S4. In a three-necked flask equipped with a stirring device, 2 g of intermediate 3 was mixed with 200 mL of a mixed solvent of tert-butanol and water (the volume ratio of tert-butanol and water was 4:1), and magnetically stirred for 2 h. After uniform dispersion, 30 mL of sodium hypochlorite was added, and the mixture was reacted at room temperature for 6 h in the dark. After the reaction was completed, the solvent was removed by reduced pressure distillation to obtain modified carbon nanotubes.

[0049] Embodiment 3

[0050] 60 g of natural latex, 20 g of polyurethane, 6 g of the modified carbon nanotubes prepared in Example 1, 3 g of antioxidant (2 g of antioxidant 1010 and 1 g of antioxidant 168) and 2 g of paraffin were mixed in a high-speed mixer, and then put into a twin-screw extruder for melt blending and extrusion at an extrusion temperature of 180° C. to obtain an antistatic skin-friendly glove material.

[0051] Embodiment 4

[0052] 70 g of natural latex, 25 g of polyurethane, 12 g of the modified carbon nanotubes prepared in Example 2, 6 g of antioxidant (4 g of antioxidant 1010 and 2 g of antioxidant 168) and 3 g of epoxidized soybean oil were mixed in a high-speed mixer, and then put into a twin-screw extruder for melt blending and extrusion at an extrusion temperature of 190° C. to obtain an antistatic skin-friendly glove material.

[0053] Embodiment 5

[0054] 80 g of natural latex, 30 g of polyurethane, 18 g of the modified carbon nanotubes prepared in Example 2, 9 g of antioxidant (6 g of antioxidant 1010 and 3 g of antioxidant 168) and 4 g of epoxidized soybean oil were mixed in a high-speed mixer, and then put into a twin-screw extruder for melt blending and extrusion at an extrusion temperature of 200° C. to obtain an antistatic skin-friendly glove material.

[0055] Comparative Example 1

[0056] Ordinary carbon nanotubes of the same mass were used to replace the modified carbon nanotubes in Example 5, and the remaining steps were the same as in Example 5 to prepare the glove material.

[0057] Comparative Example 2

[0058] The modified carbon nanotubes in Example 5 were replaced with commercially available chloramine antibacterial agent of equal mass, and the remaining steps were the same as those in Example 5 to prepare a glove material.

[0059] Embodiments 3, 4, 5, and comparative examples 1 and 2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:

[0060] The tensile strength was determined using the national standard GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”;

[0061] The surface resistivity is measured using the national standard GB / T 1410-2006 "Test method for volume resistivity and surface resistivity of solid insulating materials" (the smaller the surface resistivity, the better the conductive performance);

[0062] The national standard GB / T 31402-2015 "Test method for antibacterial performance of plastic surfaces" was used to determine the antibacterial properties and calculate the antibacterial efficiency;

[0063] The antibacterial efficiency test method is as follows: Staphylococcus aureus and Escherichia coli are used as test bacteria to inoculate the sample, and the inoculated sample is placed in an environment of 25°C and humidity greater than 85% for 24 hours, the number of live bacteria is tested, and the antibacterial efficiency is calculated; the same standard is used to determine the antibacterial rate of the sample after it is placed at room temperature for 180 days;

[0064] The measured results are shown in the following table:

[0065]

[0066] It can be seen from the above table that the mechanical properties, antistatic properties and antibacterial properties of the glove material prepared in the embodiment of the present invention are higher than those of the comparative example, and after 180 days, the antibacterial property decreases slightly and the performance is long-term and stable, which has important application value in the field of glove material technology.

[0067] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0068] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing an antistatic skin-friendly glove material, characterized in that: The method comprises the following steps: mixing natural latex, polyurethane, modified carbon nanotubes, antioxidant and dispersant in a high-speed mixer, and then putting the mixture into a twin-screw extruder for melt blending and extrusion to obtain an antistatic skin-friendly glove material.

2. The method for preparing an antistatic skin-friendly glove material according to claim 1, characterized in that: The modified carbon nanotubes are prepared by the following steps: S1. Dissolve isocyanuric acid in deionized water at room temperature under nitrogen protection, add sodium hydroxide after stirring evenly, and then slowly drop 5-chlorovaleraldehyde into a three-necked flask. Under magnetic stirring, fully react at room temperature for 12 hours. After the reaction is completed, adjust the pH to 6-7 with dilute sulfuric acid, remove the solvent with a rotary evaporator, wash, and vacuum dry to obtain intermediate 1; S2, after the intermediate 1 and N, N-dimethylformamide are stirred evenly, p-phenylenediamine and piperidine are added, stirred and mixed evenly, reacted at 65° C. for 8 h, the reaction is completed, vacuum distillation, column chromatography purification, rotary evaporation, to obtain intermediate 2; S3, mixing the carboxylated carbon nanotubes with N,N-dimethylformamide, ultrasonically treating for 30 min, then adding the intermediate 2 and dicyclohexylcarbodiimide, magnetically stirring for 2 h, placing in a 55°C water bath for ultrasonication for 2 h, then removing the water bath and magnetically stirring at room temperature for 8 h, filtering, washing, drying, and grinding to obtain the intermediate 3; S4. The intermediate 3 is mixed with a mixed solvent of tert-butyl alcohol and water, and magnetically stirred for 2 hours. After uniform dispersion, sodium hypochlorite is added, and the mixture is reacted at room temperature for 6 hours in a light-proof condition. After the reaction is completed, the mixture is distilled under reduced pressure to obtain modified carbon nanotubes.

3. The method for preparing an antistatic skin-friendly glove material according to claim 2, characterized in that: In step S1, the ratio of the amount of isocyanuric acid, deionized water, sodium hydroxide and 5-chlorovaleraldehyde is 14.1 g: 100 mL: 7.9 g: 11.9 g.

4. The method for preparing an antistatic skin-friendly glove material according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, N,N-dimethylformamide, p-phenylenediamine, and piperidine is 21.3 g:100 mL:15.2 g:15 mL.

5. The method for preparing an antistatic skin-friendly glove material according to claim 2, characterized in that: In step S3, the ratio of the amount of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate 2, and DCC is 1 g:100 mL:8.4 g:4.3 g.

6. The method for preparing an antistatic skin-friendly glove material according to claim 2, characterized in that: In step S4, the ratio of the intermediate 3, the mixed solvent of tert-butyl alcohol and water, and the sodium hypochlorite is 1 g: 100 mL: 15 mL.

7. The method for preparing an antistatic skin-friendly glove material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 60-80 parts of natural latex, 20-30 parts of polyurethane, 6-18 parts of modified carbon nanotubes, 3-9 parts of antioxidants, and 2-4 parts of dispersants.

8. The method for preparing an antistatic skin-friendly glove material according to claim 1, characterized in that: The antioxidant is prepared by compounding a hindered phenol antioxidant and a phosphite antioxidant in a mass ratio of 2:

1.

9. An antistatic skin-friendly glove material, characterized in that: Prepared according to the method according to any one of claims 1 to 8.